De novo assembly and analysis of Cassia obtusifolia seed transcriptome to identify genes involved in the biosynthesis of active metabolites. Issue 5 (4th May 2014) - Liu, Zubi; Song, Tao; Zhu, Qiankun; Wang, Wanjun; Zhou, Jiayu; Liao, Hai
Abstract: A cDNA library generated from seeds of Cassia obtusifolia was sequenced using Illumina/Solexa platform. More than 12, 968, 231 high quality reads were generated, and have been deposited in NCBI SRA (SRR 1012912). A total of 40, 102 unigenes (>200 bp) were obtained with an average sequence length of 681 bp by de novo assembly. About 34, 089 (85%) unique sequences were annotated and 8694 of the unique sequences were assigned to specific metabolic pathways by the Kyoto Encyclopedia of Genes and Genomes. Among them, 131 unigenes, which are involved in the biosynthesis and (or) regulation of anthraquinone, carotenoid, flavonoid, and lipid, the 4 best known active metabolites, were identified from cDNA library. In addition, three lipid transfer proteins were obtained, which may contribute to the lipid molecules transporting between biological membranes. Meanwhile, 30 cytochrome P450, 12 SAM-dependent methyltransferases, and 12 UDP-glucosyltransferase unigenes were identified, which could also be responsible for the biosynthesis of active metabolites. Graphical abstract: : Gene Ontology Classification for the Annotated All-unigenes of Cassia obtusifolia Seed Transcriptome.